Chronic pelvic pain: comorbidity between chronic musculoskeletal pain and vulvodynia - G. Biasi; V. Di Sabatino; A. Ghizzani; M. Galeazzi (PAGEPress Publications, 2014)
Chronic pelvic pain (CPP) is a common condition that has a major impact on the quality of life of both men and women. Male CPP is usually attributable to well-defined urogenital conditions (most frequently infectious/non infectious prostatic diseases) or musculoskeletal or bowel diseases, whereas the features of female CPP are much more complex and are of particular clinical and epidemiological importance. It is a multifactorial syndrome that can be due to diseases of the urogenital, gastrointestinal, or musculoskeletal systems, or to neurological or neuropsychiatric disorders. It is not always easy to identify its predominant pathogenesis, although it often occurs as a central sensitization syndrome triggered by an initial stimulus which is no longer detectable and only manifests itself clinically through pain. In this respect, there are some very interesting relationships between vulvodynia and fibromyalgic syndrome, as identified in a preliminary study of women with chronic musculoskeletal pain in which it was demonstrated that vulvar pain plays an important role, although it is often overlooked and undiagnosed.